“THE IMPACT OF FAMILY UPBRINGING ON THE DEVELOPMENT OF EMOTIONAL INTELLIGENCE” - Aymuratova Zliyxa Jan'abay qizi (Western European Studies, 2025)
This article explores the impact of family upbringing on the development of emotional intelligence (EI). Emotional intelligence refers to a person’s ability to recognize, manage, and respond appropriately to their own emotions and those of others. The article examines how the emotional environment within the family, parental communication styles, expressions of love and care, and approaches to conflict resolution play a crucial role in shaping a child’s EI. It also outlines the core components of emotional intelligence and illustrates how each is influenced by family dynamics. Supported by psychological research, the article emphasizes the vital role of family upbringing in fostering emotionally and socially competent individuals
Keywords: family upbringing; emotional intelligence; child development